Identification of molecular mechanism of the anti-lung cancer effect of Jin Ning Fang using network pharmacology and its experimental verification. Issue 1 (31st December 2022) - Wu, Chunxiao; Yu, Qiquan; Shou, Weizhen; Zhang, Kun; Li, Yang; Guo, Wentao; Bao, Qi
Abstract : Jin Ning Fang (JNF), a classic Chinese medicine formula, is widely used to treat lung cancer. However, its molecular mechanism remains unclear. Thus, we aimed to explore the pharmacological mechanisms of JNF against lung cancer. JNF targets and lung cancer-related genes were derived from public databases. Key compounds, potential therapeutic targets, and pathways were determined via bioinformatics analyses. Further, molecular docking, in vitro experiments, and real-time PCR were performed to verify the findings. A total of 27 active compounds and 25 genes were selected. Pharmacological network revealed that quercetin, calcium carbonate, and beta-sitosterol might be candidate agents; ESR1, AR, AKT1, FDPS, PIM1, VCAM1, SLC29A1, NQO1, and ANPEP could be potential drug targets. These genes were involved in apoptosis pathway. Docking analysis showed that beta-sitosterol combined well with AKT1, AR, and ESR1. In vitro experiments confirmed that JNF could inhibit proliferation and promote apoptosis of A549 cells. JNF treatment inhibited the level of FDPS, PIM1, VCAM1, SLC29A1, NQO1, and ESR1, while increased the level of AR and ANPEP . This study illuminated that JNF exerts anti-lung cancer effects through regulating multiple targets and pathways, and the identified genes may be used as potential therapeutic targets for lung cancer.